2020
DOI: 10.1177/0361198120917384
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Subway Bottleneck Mitigation Strategies using Microscopic, Agent-Based Simulation

Abstract: Many subway systems operating near capacity face challenges in meeting reliability and level of service targets. This paper examines the effectiveness of various strategies to relieve congestion and increase capacity using a microscopic, agent-based, urban heavy rail simulation model. The Massachusetts Bay Transportation Authority’s (MBTA) Red Line serves as the testbed for the analysis. The Red Line operates very close to its capacity. Bottlenecks on the Red Line and possible strategies to mitigate them are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…To apply the framework described in Figure 2, the model derived in the previous section is combined with an urban rail simulation model (SimMETRO) to assess the risk of transmission. SimMETRO is a microscopic, agent-based stochastic simulation model ( 25 , 26 ). It is detailed and designed for heavy rail system performance analysis, operations planning, signaling system evaluation, real-time control strategies evaluation and refinement, and operator-in-the-loop training.…”
Section: Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…To apply the framework described in Figure 2, the model derived in the previous section is combined with an urban rail simulation model (SimMETRO) to assess the risk of transmission. SimMETRO is a microscopic, agent-based stochastic simulation model ( 25 , 26 ). It is detailed and designed for heavy rail system performance analysis, operations planning, signaling system evaluation, real-time control strategies evaluation and refinement, and operator-in-the-loop training.…”
Section: Applicationmentioning
confidence: 99%
“…A detailed dwell time model is used to determine a train’s dwell times at stations as a function of the number of boarding and alighting passengers. SimMETRO has been calibrated and validated in previous studies ( 26 , 27 ) using calibration and validation methods reported in the literature ( 26 – 29 ).…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The orientation of the entrances affects passenger flow and station accessibility, as well as lighting and ventilation [19]. The size of the portal, or entrance and exit dimensions, directly impacts congestion levels and passenger throughput [20]. Navigational clarity is crucial in subway environments [21].…”
Section: Investigating Potential Influencers On Passenger Satisfactio...mentioning
confidence: 99%